Is Robotic-Assisted Unicompartmental Knee Arthroplasty Compared to Manual Unicompartmental Knee Arthroplasty Associated With Decreased Revision Rates? An Updated Matched Cohort Analysis - George Guild, MD; Joseph Schwab, MD; Bailey J. Ross, MD; Mary Jane McConnell, BS; Farideh Najafi, MD; Thomas L. Bradbury, MD (Arthroplasty Today)
Background: Despite increased utilization of robotic assistance during unicompartmental knee arthroplasty (UKA), its impact on postoperative outcomes remains unclear. This study aimed to compare rates of postoperative revision and complications among patients undergoing robotic-assisted UKA (RA-UKA) versus manual UKA. Methods: A retrospective matched cohort study was performed. Trends analysis of the annual proportion of RA-UKA between 2010 and 2021 was performed, and RA-UKA patients (n = 3976) were matched 1:3 with manual UKA patients (n = 11,766) across age, sex, Elixhauser Comorbidity Index, and comorbidities. Rates of 2-year prosthesis-related complications were compared between the matched cohorts using multivariable logistic regression. Results: The annual proportion of UKA procedures performed with robotic assistance trended significantly upward (1.51% to 5.19%, P < .001). Within 2 years postoperatively, the RA-UKA cohort exhibited significantly lower rates of aseptic revision (1.84% vs 2.37%; odds ratio: 0.76; P = .040) and aseptic loosening (0.13% vs 0.42%; odds ratio: 0.32; P = .010). Total cost for the index UKA was significantly higher for the RA-UKA cohort ($10,321 vs $7,366; P < .001). Conclusions: There has been a marked increase in utilization of RA-UKA. Compared to matched manual UKA, RA-UKA had lower rates of revision and aseptic loosening at 2-year follow-up, but at a higher total cost for the index procedure. Further research exploring the use of robotics in UKA with attention to patient outcomes and cost is crucial for defining its evolving role in orthopaedic surgery.